2022
DOI: 10.1038/s41598-022-19377-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of n-octanol on impurity removal by reverse flotation of magnesite ore

Abstract: Dodecylamine is one of the most commonly used amine collectors for the reverse flotation of magnesite ore. Through a combination of experimental research and computational simulation, the effect of n-octanol on the removal of impurities by the reverse flotation of magnesite ore was studied. The test results show that when the dosage of dodecylamine was 60 mg/L, the flotation rates of magnesite and dolomite were 59.53% and 58.02%, respectively, and the flotation rate of quartz was 97.60%. In the presence of n-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Through DFT calculations, Zhong et al [86] and Tang et al [87] investigated the adsorption mechanisms of α-chloro-oleate acid and cetyl phosphate, respectively, as collectors on a magnesite surface. Li et al [88] compared the effects of dodecylamine and n-octanol as collectors on the removal of impurities in the reverse flotation of magnesite by combining experimental studies and computational simulations. It was shown that the dissolved Ca 2+ ions in dolomite weaken the selectivity of anion flotation, which is one of the reasons for the difficulty in separating dolomite and magnesite.…”
Section: Other Non-ferrous Oxide Mineralsmentioning
confidence: 99%
“…Through DFT calculations, Zhong et al [86] and Tang et al [87] investigated the adsorption mechanisms of α-chloro-oleate acid and cetyl phosphate, respectively, as collectors on a magnesite surface. Li et al [88] compared the effects of dodecylamine and n-octanol as collectors on the removal of impurities in the reverse flotation of magnesite by combining experimental studies and computational simulations. It was shown that the dissolved Ca 2+ ions in dolomite weaken the selectivity of anion flotation, which is one of the reasons for the difficulty in separating dolomite and magnesite.…”
Section: Other Non-ferrous Oxide Mineralsmentioning
confidence: 99%